Rapid Alcoholysis of Jatropha Curcas Oil for Biodiesel Production Using Ultrasound Irradiation - Muh. Irwan; Hamdani Saidi; M. A. Rachman; Ramli Ramli; Marlinda Marlinda (Department of Chemical Engineering - Diponegoro University, 2017)
The biodiesel synthesis through alcoholysis process of triglyceride from Jatropha curcas using different type of alcohol, such as: methanol, ethanol, isopropyl alcohol and tert-butanol, was conducted in the presence of potassium hydroxide (KOH) as catalyst under 35 kHz frequency ultrasound irradiation. The optimum conditions, such as: alcohol to jatropha oil molar ratio, concentration of catalyst, reaction temperature, and reaction time, were found to be 7:1 of alcohol to jatropha oil molar ratio, 0.5 % of KOH, temperature of reaction at 35 0C, within the reaction times of 15 minutes. The results obtained for the different types of alcohol were 62.77 %, 57.93 %, 51.64 %, and 46.77 % for methanol, ethanol, isopropyl alcohol, and tert-butanol, respectively.